Analisis Peran Mindfulness Islami dalam Mengatasi Overthinking pada Remaja Gen Z - Ari Sofia; Mujiyati; Dayu Rika Perdana; Nurwahidin, Muhammad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Overthinking among Generation Z adolescents has emerged as a critical psychological issue, driven by digital exposure, academic pressure, and social demands, ultimately impacting mental health. The lack of interventions integrating Islamic spiritual values has worsened this condition. This study aims to examine the effectiveness of Islamic mindfulness—combining modern awareness techniques with dzikir, tafakkur, and muhasabah practices—in reducing overthinking and improving emotional regulation. A participatory community-based approach was applied to 25 Muslim Gen Z students (aged 18–24) in Metro City, active in religious forums and showing symptoms of overthinking. Data were collected through in-depth interviews, training observations, and participant reflections, then analyzed thematically. Anticipated results include the development of an evidence-based Islamic mindfulness module, a decrease in overthinking symptoms, and improved spiritual-emotional resilience. Outputs cover scientific publications, digital educational content, and the establishment of a mentally and spiritually aware youth community.